Assessment of Physicochemical Parameters of Harvested Rainwater in Hamuhambo Town Council Rubanda District. - Atuheire, Israel (Kabale University, 2025)
Harvesting rainwater is a reliable alternative for the local people globally who have no access to centralized and piped water systems due to geographical location and economic pressure. The study accessed some of the physicochemical parameters such as pH, Temperature, turbidity, Electrical conductivity, Dissolved Oxygen, and TDS across eight stations that included 3 community tanks (at a primary school, at a church, and a health center III hospital) and 5 individual household tanks by sampling once after eight weeks of harvest and storage of rainwater, to establish the water quality as there is a risk of contamination during harvesting and storing. However, this rainwater is mainly used directly for consumption and domestic use without any post-harvest treatment to improve the water quality since it is commonly done individually without any specialist knowledge and standard guidelines. The Mean: SD values for the physicochemical parameters measured PH: 8.8±1.5, Temperature: 21.7±1.0 (°c), EC: 168.8±86.3 (µ/cm), DO: 6.2±1.8 (mg/l), TDS: 87±47 (mg/l) and turbidity: 6.1±15.9 NTU were within the acceptable limits for portable water in reference to WHO and UNBS (Table 2), therefore I conclude that even after harvested rainwater has been stored for some time, its quality is not affected and it is thus fit for consumption and domestic use. There were no significant variations in the variables accessed apart from an abnormally high turbidity value at ST 05 where the sample was picked from the minimal water remaining on the floor that contained a lot of total dissolved solids suggesting regular cleaning of the RWHS at the beginning of each rain season, a first flush of 15 minutes at the beginning of the rain and installation of proper pre-filtration mechanisms. It is important to fence the underground RWHS to keep away children who may contaminate the water. Excavation of drainage channels where they are absent for example ST 03 and ST 08 and regular maintenance for those station (s) who have ST 01.